2006
DOI: 10.1111/j.1365-2745.2006.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

The controversy over traits conferring shade‐tolerance in trees: ontogenetic changes revisited

Abstract: Summary1 Successional replacement of intolerant species by shade tolerators along gapunderstorey gradients is commonly associated with increasingly higher low-light carbon acquisition capacities of more tolerant species. This doctrine has recently been challenged because of evidence demonstrating larger leaf dry mass per unit area ( M A ), lower photosynthetic capacities and inferior whole plant relative growth rates (RGR) in both high and low irradiance in seedlings of shade-tolerators. However, as the indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(137 citation statements)
references
References 39 publications
7
126
2
2
Order By: Relevance
“…Lusk and Warton, 2007;Niinemets, 1999aNiinemets, , 2006Thomas and Winner, 2002). In the present study we observed a significant increase of LMA with the sequence of ASDs in juvenile T. melinonii and to a lesser extent D. guianensis.…”
Section: Dicorynia Guianensissupporting
confidence: 64%
See 2 more Smart Citations
“…Lusk and Warton, 2007;Niinemets, 1999aNiinemets, , 2006Thomas and Winner, 2002). In the present study we observed a significant increase of LMA with the sequence of ASDs in juvenile T. melinonii and to a lesser extent D. guianensis.…”
Section: Dicorynia Guianensissupporting
confidence: 64%
“…The two species are known to be rather shade-intolerant and the observed differences cannot be attributed to different ecological requirements. Moreover, to characterize shade tolerance as a trait, there is a need to scale up from leaf to at least branch level (if not canopy level) and to take into account potential effects of leaf life span (Lusk and Warton, 2007;Lusk et al, 2008;Niinemets, 2006;Valladares and Niinemets, 2008). Taking into account such integrative traits would be a target for future developments in the assessment of potential interactions between ontogeny and irradiance on tree physiology and carbon balance.…”
Section: Difference In Irradiance-induced Plasticity Of Leaf Traits Amentioning
confidence: 99%
See 1 more Smart Citation
“…Gaps, which represent an important facilitator of natural regeneration, may not occur. Many individuals need adjustments to heterogeneous light conditions in understory and it is expressed on leaf morphology (Niinemets 2006). However, morphological variations in the individuals the seedling and adult stages have been little explored.…”
Section: Introductionmentioning
confidence: 99%
“…Although the knowledge about the shade tolerance of the plants goes back to the 18th century, there are still controversies about what are the main morphological traits of tolerant species (Niinemets 2006). The knowledge about the adaptations to shade conditions is based mainly on the development of seedlings and the observed patterns are influenced by the interspecific variation of seed size (Sack et al 2006;Valladares and Niinemets 2008).…”
Section: Introductionmentioning
confidence: 99%